تطبيق البرنامج "المخيم العربي" في تعليم اللغة العربية بمعهد دار الزهراء ماليزيا - Lutpiasari, Lutpiasari; Jamaluddin, Jamaluddin; Ibrahim, Rabiatul Adawiyah (Kalimatuna: Journal of Arabic Research, 2024)
This research aims to find out that Arabic Camp can be a major factor in the success of learning foreign languages, especially Arabic. The method used is a descriptive qualitative method. This research was conducted at the Daruzzahra Islamic boarding school in Malaysia. Data collection was carried out by means of observation and interviews. The research data respondents were three students and one teacher. The results of the research show that the application of Arabic Camp is effective in learning Arabic at the Daruzzahra Islamic boarding school in Malaysia. The students' responses were good and satisfied in interviews regarding the implementation of Arabic Camp. So, it can be said that the application of Arabic Camp was successful in increasing students' interest in learning Arabic.